Foreshadows and Symbols in The Brussels Companys Main Office in Joseph Conrads Heart of Darkness - Ena, Ouda Teda; Yulia, Made Frida (LLT Journal: A Journal on Language and Language Teaching, 2012)
Joseph Conrads Heart of Darkness unveils a story about a journey to the inner self to find the mysteries of human mind. The way the writer presents his story is very intriguing in that he makes of use of many foreshadows and symbols. This paper  attempts to examine the foreshadows and symbols which Conrad uses in this novella;however, the discussion is limited to the ones that appear in The Brussels CompanysMain Office.